Plan de comunicación online para difundir el servicio de mantenimiento preventivo de vehículos entre asesores técnicos y clientes de la empresa induauto, matriz Guayaquil - Maldonado Bayas, José Alexander (2018)
The title work "Online Communication Plan to disseminate the vehicle preventive aintenance service between technical advisors and clients of the company Induauto, Matrix - Guayaquil", highlights the importance of investigating, identifying, analyzing the internal and external deficiencies that limit the digital communication, to propose the use of online channels with the greatest impact and acceptance for the dissemination of policies, trategies and services that improve the relationship between the company and customers. At present, digitized life is daily, communication through email, text messages, chat, in which information platforms are used, programs whose contents become efficient and effective service guides and applications that allow the coordination of virtual processes that support improving relationships between companies and services. With the aforementioned background, the implementation of quantitative and qualitative research was considered, based on surveys and personal interviews, in which the importance of digital media in the daily life of clients was exposed, whose results showed that companies should consider Changes in communication to adapt to them and use them better…….